Effect of Emblica Officinalis (amloki) on iron status in pregnant women with iron deficiency anaemia - Akter, Tahmina; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2019)
Background: Common clinical practice of prescribing Iron supplementation for Iron deficiency anemia (IDA) in pregnancy is associated with a number of side effects. Emblica officinalis (amloki) is a well known dietary supplement used by traditional practitioners to treat anemia. Objective: To evaluate the effects of oral supplementation of Emblica officinalis on iron status in pregnant women with IDA. Methods: This prospective interventional study was carried out in the Department of Physiology, Dhaka Medical College (DMC), Dhaka from July 2016 to June 2017 on 43 pregnant women aged 18 to 36 years between 13th to 20th weeks of gestation with IDA. They were recruited from the Out-patient department of Obstetrics and Gynaecology, DMC Hospital. Among them 24 were supplemented with amloki and iron (IAS) and 19 women received only iron supplementation (IS). Study variables were estimated at the baseline and after 45 days of supplementation. Serum iron, ferritin and Total iron binding capacity (TIBC) were estimated following standard laboratory methods. Data were expressed as mean ± SD. Paired and Unpaired Student’s t-test were used for statistical analysis. Results: Serum iron levels were significantly higher (p<0.001) and serum TIBC were significantly lower (p<0.001) in both groups after supplementation compared to their baseline value. But post supplementation serum ferritin level was significantly higher (p<0.01) only in IAS group compared to that of the baseline. Again, after intervention, serum iron level was significantly higher (p<0.05) and serum TIBC was significantly lower (p<0.01) in IAS group when compared with those of IS group. Conclusions: Data concluded that oral Emblica officinalis supplement along with iron was more effective than only iron supplementation to improve serum iron status in pregnant women with IDA. J Bangladesh Soc Physiol. 2019, June; 14(1): 1-6